Comparative Study of Patient-Reported Outcomes with Different Aesthetic Restorative Materials in Anterior Teeth - Ipsita Singh; Noora O. E. S. Al Suwaidi; Manish Pisarla; Bharathi Chundi; Manawar A. Mansoor; Hina N. Abdul; Trupti G. Makwana (Journal of Pharmacy and Bioallied Sciences)
Objective: The study aims to compare patient-reported outcomes for aesthetic restorations in anterior teeth using composite resins, glass ionomer cements (GICs), and ceramic-based restorations. Patient satisfaction regarding aesthetics, functionality, durability, and overall experience was evaluated. Materials and Methods: This prospective cohort study included 180 patients (aged 18–65 years) who required anterior aesthetic restorations. Patients were randomly assigned to receive either composite resin, GIC, or ceramic restorations. Satisfaction with aesthetics, comfort, and durability was measured using a visual analog scale (VAS) at 1-, 6-, and 12-month post-treatment. Statistical analysis was performed using ANOVA, with a P value < 0.05 considered significant. Results: Ceramic restorations scored the highest for aesthetics (VAS 9.1), functionality (VAS 9.0), and durability (5% reported issues). Composite resins had lower durability (15% reported issues) but scored well in aesthetics (VAS 8.2). GICs had the lowest overall satisfaction, with 25% reporting durability issues. Overall satisfaction was highest for ceramics (94%), followed by composites (85%) and GICs (68%). Conclusion: Ceramic restorations offer superior aesthetic and functional outcomes. Composite resins provide a cost-effective option with acceptable aesthetics, while GICs were rated lower due to their limited durability and aesthetics.